Invasion of Fall armyworm [Spodoptera frugiperda (JE Smith, 1797) (Lepidoptera: Noctuidae)] (JE Smith ,1797) (Lepidoptera: Noctuidanead) Management Strategies in Maize Fields of Nepal - Shobha Pokhrel; Gautam Bahadur Khadka; Dolma Diki Sherpa; Neha Sah; Ishan Gautam; Sachindra Dev Upadhyaya; Rashmi Khanal (Turkish Journal of Agriculture: Food Science and Technology, 2022)
The fall armyworm [Spodoptera frugiperda, (JE Smith, 1797) (Lepidoptera: Noctuidae)] is a polyphagous pest native to tropical and subtropical regions of America. After it was detected for the first time in Nepal in the Nawalpur area on 9th May 2019, it has become a major threat in maize fields even though it has over 80 host species to proceed its life cycle. Due to its migratory nature, FAW moth can travel up to 500 km before oviposition, and infestation of its larva has resulted in vast devastation of the vegetative as well as reproductive parts of plants causing significant yield loss in maize. A mature larva possesses a dark head with an upside-down pale Y-shaped marking on the head area and black four spots that are arranged in a square on the second last body segment. This paper audits the executive choices (avoidance, observing, push-pull, cultural, biological, organic, chemical, and integrated techniques to incorporate in FAW susceptible areas) that apply to smallholder farmers who do not have the monetary asset to buy compound pesticides and other costly control instruments. For the majority of Nepalese farmers with low resources and small landholding, push-pull technology is beneficial and applicable. Botanicals that have bioactive chemical compounds, insecticidal, pest repellent properties are environment-friendly and degradable, readily available in tropical and subtropical regions of Nepal. The assessment of the efficacy of implemented management practices against FAW has revealed that implementation of more than one method of management practices showed the least percentage of infestation as compared to the individual method.